Quizizz: Alternatif Penilaian di Masa Pandemi Covid-19 - Wahyudi, Wahyudi; Rufiana, Intan Sari; Nurhidayah, Dwi Avita (Universitas Dr. Soetomo, 2020)
Abstract During the current Covid-19 pandemic, this presents a special challenge for the world of education. Learning must be carried out, so online learning is carried out. Teachers must design effective learning for students. Besides, an effective online learning assessment must also be considered, because it is used as an evaluation of further learning. This paper hopes to provide additional information about alternative learning assessments during the Covid-19 pandemic. This research is a literature review. Researchers collect, process, and conclude data (information) from various relevant sources. The results of this study are that QUIZIZZ can be used as an alternative assessment of learning, especially mathematics learning during the Covid-19 pandemic. QUIZIZZ is attractively designed and not monotonous, and based on games. QUIZIZZ is an online application that makes it easy and summarizes for teachers in effective learning assessments. QUIZIZZ can be accessed at https://quizizz.com/ . Keywords: QUIZIZZ, daring, assessment of learning, mathematics learning, Covid-19 Pandemic. Abstrak Pada masa pandemi Covid-19 sekarang ini, memberikan tantangan khususnya bagi dunia pendidikan. Pembelajaran harus tetap dilaksanakan, sehingga dilakukanlah pembelajaran daring. Guru harus mendesain pembelajaran yang efektif bagi siswa. Selain itu, penilaian pembelajaran daring yang efektif juga harus diperhatikan, karena digunakan sebagai evaluasi pembelajaran selanjutnya. Harapan dari tulisan ini adalah sebagai tambahan informasi mengenai alternatif penilaian pembelajaran di masa pandemi Covid-19. Penelitian ini merupakan penelitian kajian pustaka. Peneliti mengumpulkan, mengolah, dan menyimpulkan data (informasi) dari berbagai sumber yang relevan. Hasil penelitian ini adalah QUIZIZZ dapat digunakan sebagai alternatif penilaian pembelajaran khususnya pembelajaran matematika di masa pandemi Covid-19 ini. QUIZIZZ terdesain dengan menarik dan tidak monoton, dan berbasis games. QUIZIZZ sebagai aplikasi online yang memudahkan dan merangkum bagi guru dalam penilaian pembelajaran yang efektif. QUIZIZZ dapat di akses di https://quizizz.com/. Kata Kunci: QUIZIZZ, daring, penilaian pembelajaran, pembelajaran matematika, pandemi Covid-19.